2009
DOI: 10.1111/j.1468-0394.2008.00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and delineation of P and T waves in 12‐lead electrocardiograms

Abstract: This paper presents an efficient method for the detection and delineation of P and T waves in 12-lead electrocardiograms (ECGs) using a support vector machine (SVM). Digital filtering techniques are used to remove power line interference and baseline wander. An SVM is used as a classifier for the detection and delineation of P and T waves. The performance of the algorithm is validated using original simultaneously recorded 12-lead ECG recordings from the standard CSE (Common Standards for Quantitative Electroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…There can be no CP violation in the two flavour case in vacuum as the unitary matrix in two flavour case can always be made real. In matter with varying density, this need not be the case (for geometric visualization, see [45,46]). Some theoretical consequences of the value of CP violating phase were discussed in [47].…”
Section: Frameworkmentioning
confidence: 99%
“…There can be no CP violation in the two flavour case in vacuum as the unitary matrix in two flavour case can always be made real. In matter with varying density, this need not be the case (for geometric visualization, see [45,46]). Some theoretical consequences of the value of CP violating phase were discussed in [47].…”
Section: Frameworkmentioning
confidence: 99%
“…This makes it challenging to isolate the value of genuine CP violating phase δ in SI case from the fake effects and there are several suggestions to tackle the problem [7,8]. The geometric visualization of CP conservation and CP violation for the two flavour neutrino case was demonstrated in [44,45].…”
Section: Genuine and Fake Cp Violation Due To Earth Matter Effects -Smentioning
confidence: 99%
“…It is found that this combination offers subsets yielding similar or much better accuracies than using the full set of genes. Mehta et al (2009), in their paper 'Detection and delineation of P and T waves in 12-lead electrocardiograms', present an efficient method for the detection and delineation of P and T waves in 12-lead electrocardiograms using a support vector machine. Digital filtering techniques are used to remove power line interference and baseline wander.…”
Section: The Papersmentioning
confidence: 99%